Adhesive lipophilic gels delivering rapamycin prevent oral leukoplakia from malignant transformation - Yuqi Du; Tiannan Liu; Tingting Ding; Xin Zeng; Qianming Chen; Hang Zhao (Materials Today Bio)
Oral leukoplakia (OLK) is the most emblematic oral potentially malignant disorder that may precede the diagnosis of oral squamous cell carcinoma (OSCC) and has an overall malignant transformation rate of 9.8 %. Early intervention is crucial to reduce the malignant transformation rate from OLK to OSCC but the lack of effective local pharmaceutical preparations poses a challenge to clinical management. Rapamycin is speculated to prevent OLK from carcinogenesis and its inherent lipophilicity facilitates its penetration into stratum corneum. Nevertheless, hydrophilic hydrogels frequently encounter challenges when attempting to deliver lipophilic drugs. Furthermore, the oral cavity presents a complex environment defined by oral motor functions, saliva secretion cycles, dynamic fluctuations, and protective barriers comprising mucus and lipid layers. Consequently, addressing issues of muco-penetration and muco-adhesion is imperative for developing an effective drug delivery system aiming at delivering rapamycin to target oral potentially malignant disorders.Here, a dual-function hydrogel drug delivery system integrating adhesion and lipophilicity was successfully developed based on polyvinyl alcohol (PVA) and dioleoyl phosphatidylglycerol (DOPG) via dynamic boronic ester bonds. Rheological experiments based on orthogonal design revealed that PVA-DOPG hydrogels exhibited ideal adhesive strength (around 6 kPa) and could adhere to various surfaces in both dry and wet conditions. PVA-DOPG hydrogels also significantly promoted lipophilic molecules’ penetration into stratum corneum (integrated fluorescence density of 6.95 ± 0.52 × 106 and mean fluorescence depth of 0.96 ± 0.07 mm) of ex-vivo porcine buccal mucosa (p < 0.001). Furthermore, PVA-DOPG hydrogels incorporating rapamycin inhibited malignant transformation of OLK mouse model induced by 4-Nitroquinoline N-oxide (4-NQO), distinct improvements in survival (the neoplasm incidence density at the 40th day is 0.0091) (p < 0.05), decrease in neoplasm incidence density of 36.36 % and inhibition rate in neoplasm volume of 75.04 ± 33.67 % have been demonstrated, suggesting the hydrogels were valuable candidates for potential applications in the management of OLK.